Development and characterization of bionanocomposites from electro spun collagen/ phbv/ chitosan/ hypericum perforatum extract for potential wound healing applications - Moutsinga, Elvy Greg Bienvenu Kebila (My University, 2020)
A wound can be defined as the loss of the integrity of anatomical tissues caused by exposure to various factors such as lacerations, extreme heat or corrosives. The formation of the wound is generally followed by wound healing which is a complex physiological process that involves many different components. It is known that inflammatory response is the starting point of the synthesis of dermal enzymes leading to degradation of extracellular matrix components. Hyaluronidase depolymerized hyaluronic acid, elastin fibers and fibrin are being hydrolyzed by elastase, and collagenase (matrix metalloproteinases-1) breaks the type I collagen and affects the wound healing process. Since ancient times, various methods have been employed to treat wounds and many of those generally include the covering of the wound area with various materials and plants. In recent years, biopolymers and plant extracts used in combinations as perfect candidates for novel wound dressing materials due to their superior properties when compared with classical wound dressings such as gauze. In this study collagen and chitosan was extracted from shrimp shell waste material and characterized by FTIR spectra. Hypericum Perforatum was macerated with ethanol to obtain plant extract. Electrospinning of the PHBV/ Collagen/ Chitosan and Hypericum perforatum extract was done using 1,1,1,3,3,3,-hexafluoroisopropanol (HFIP) as a solvent. Obtained material characterized by FTIR and SEM. The data obtained from this work suggest that shrimp shell waste is a perfect source to obtain biomaterials such as collagen and chitosan which can be used to produce nanomaterials for biotechnological applications.

Yara genellikle derinin, kesilmeler, aşırı sıcak veya aşındırıcı maddeler gibi çeşitli faktörlere maruz kalmasının neden olduğu anatomik dokuların bütünlüğünün bozulması olarak tanımlanabilir. Yaranın oluşumunu genellikle birçok farklı bileşeni içeren karmaşık bir fizyolojik süreç olan yara iyileşmesi izler. Enflamatuar tepkinin, hücre dışı matris bileşenlerinin bozulmasına yol açan dermal enzimlerin sentezini hızlandırdığı bilinmektedir. Hyaluronidaz; hyaluronik asidi, elastaz; fibrin ve elastin liflerini ve kolajenaz (matris metaloproteinaz-1) ise özellikle tip I kolajeni hidroliz ederek yara iyileşmesini etkiler.Eski zamanlardan beri, yaraları tedavi etmek için çeşitli yöntemler kullanılmıştır ve bunların çoğu genellikle yara bölgesinin çeşitli materyaller ve bitkilerle kaplanmasını içerir. Son yıllarda, biyopolimerler ve bitki ekstrelerinden oluşan farklı kombinasyonlar, gazlı bez gibi klasik yara örtüleri ile karşılaştırıldığında gösterdikleri üstün özellikler nedeniyle, yeni yara örtü malzemeler için mükemmel adaylar olarak ortaya çıkmışlardır. Doğal kaynaklardan ve sentez yolu ile elde edilebilen biyopolimerlerin, farmasötik, biyomedikal, terapötik ve yara iyileştirici malzemeler olarak kullanımları önemli bir araştırma alanıdır.Bu çalışmada, karides kabuğu atıklarından kolajen ve kitosan ekstrakte edilmiş ve FTIR spektrumları ile karakterize edildi. Hypericum Perforatum, bitki ekstresi etanol ile maserasyon yöntemi ile elde edildi. PHBV / Kolajen / Kitosan ve Hypericum perforatum ekstresi karışımı çözücü olarak 1,1,1,3,3,3, -heksafloroizopropanol (HFIP) kullanılarak gerçekleştirildi ve elde edilen biyomateryal FTIR ve SEM ile karakterize edildi. Bu çalışmanın sonuçları, karides kabuğu atıklarının, biyoteknolojik uygulamalar için kullanılabilecek kolajen ve kitosan gibi biyopolimerlerin elde edilmesinde mükemmel bir kaynak olduğunu ortaya koymaktadır.
PHBV/ kolajen/ kitosan/ hypericum perforatum ekstresi biyonanokompozitlerinin potansiyel yara iyileşmesi uygulamaları için elektrospin yöntemi ile üretilmesi ve karakterizasyonu
Keywords: Biyonanokompozit; Chemistry; Chitosan; Collagen; Hypericum perforatum extract; Hypericum perforatum özü Bionanocomposites; Kimya; Kitosan; Kolajen; PHBV